OPTIMIZATION ADSORPTION OF HEXAVALEN CHROMIUM (CR-VI) IN ACTIVATED CARBON (MICROWAVE-ASSISTED ZNCL2 CHEMICAL-ACTIVATION) USING TAGUCHI METHOD - Atiqa Rahmawati; Fadzkurisma Robbika; Yuafni (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2023)
The issue of heavy metal pollution is a significant concern in the environmental. Hexavalent chromium (Cr(VI)) is hazardous heavy metal when it is discharged and expands within ecosystem. Cr(VI) is a hazardous compound that high susceptibility to oxidation and mutagenic. The tannery industry generates hexavalent chromium in its liquid waste. Managing Cr(VI) liquid waste could use the adsorption technique with activated carbon. In this study the activation of activated carbon using microwave-assisted ZnCl2 chemical activation. The activated carbon used for adsorbing the Cr(VI). The objective of this study was to ascertain the optimum parameters for the adsorption of Cr(VI) utilizing activated carbon. The optimization method is Taguchi, which incorporates three factors: A (pH), B (activated carbon dosage), and C (agitation). The result of optimization is pH 2; 0,4 g activated carbon dosage, and agitation 20 rpm, which the optimal response was 16.7498 mg/L. The analysis using the desirability obtained desirability value of 1. The ANOVA results indicate that the pH significant on the response. The adjusted R-square is 0.9667 and predicted R-square is 0.8668. It can be concluded that the model and actual conditions has slighly discrepancies. Then, the regression equation from the model can be estimate the actual value.